Glandula Tiroid Problem: Literature Review - Muhammad Zaki Abdul Hafiz; Daan Khambri (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Thyroid cancer is the most common endocrine system neoplas m . Based on the